A Place of Love and Care Dilemmas of Protestant Diakonia in the Middle East - Saane, Wilbert van (Transformation, 2025)
As they engage in diakonia, Protestant churches in the Levant face several dilemmas. The first dilemma is related to the overwhelming needs and the sectarian makeup of society. Should they serve their faith community first, or meet needs irrespective of religious background? Another dilemma emerges in relation to resources, especially financial resources, many of which are supplied by partner churches and organisations. A third dilemma is to what extent the churches can advocate human rights while maintaining good relations with the civil authorities. This article offers an analysis of these dilemmas in light of the needs-based, assets-based, and rights-based approaches in diaconal studies. It also relates the diaconal praxis of the Protestant churches in the Middle East to recent ecumenical theory on diakonia. The main argument is that the diaconal actors preserve inclusive places of love and care as a form of mission from the margins.